A Novel Near‐IR Effective Pyrene‐Based Donor–Acceptor Electrochrome. Issue 8 (23rd February 2015) - Sefer, Emre; Hacioglu, Serife O.; Tonga, Murat; Toppare, Levent; Cirpan, Ali; Koyuncu, Sermet
<x xml:space="preserve">Abstract</x> In this work, a novel donor–acceptor electrochromic monomer (3HTP), containing a pyrene subunit connected to a quinoxaline acceptor bridge, is synthesized. The corresponding polymer, poly‐(3HTP), is directly deposited onto an indium tin oxide (ITO)/glass surface via an electrochemical process. Atomic force microscopy (AFM) images reveal that the electrochemically deposited poly‐(3HTP) has a smooth surface due to self‐assembly of the planar pyrene subunit. Electrochemical and optical properties are investigated via cyclic voltammetry and UV–vis absorption measurements. The polymer film shows a multielectrochromic feature at both anodic and cathodic regimes. Poly‐(3HTP) exhibits a strong near‐infrared (NIR) absorption at the oxidized state with an optical contrast of 88% (at 1800 nm), a very fast response time of 0.5 s and fast switching times, and long‐term stability. Density functional theory calculations reveal that the molecule has a high planarity, and the NIR absorption arises from a strong intramolecular charge transfer from the polymer backbone to the planar pyrene subunit. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>